Challenging the aid paradigm Western currents and Asian alternatives - SoÌ?rensen, Jens Stilhoff (Rethinking international development series., 2010)
"Challenging the Emerging Aid Paradigm critically examines central aspects of Western international aid policy, while at the same time exploring non-western especially Chinese aid and assesses to what extent these may be competitive or complementary"-- Provided by publisher.